Pengaruh Penggunaan Celebrity Endorser Terhadap Implusive Buying Behavior Konsumen (Survey pada Scarlett Body Whitening di Kota Bandung, Indonesia) - Azzahra, Latifah; Nursholehah, Nabilah (International Journal Administration, Business & Organization, 2022)
Scarlett Body Whitening is a brand from Indonesia released by Felicya Angelista which is famous for its brightening product variants. One of the promotions carried out by Scarlett Body Whitening is using a celebrity endorser. Celebrity endorser is an advertisement with the support of a celebrity which is believed to make it easier for consumers to remember the product and can accelerate the emergence of brand awareness of the product so as to create high consumer buying interest in beauty products. Seeing the importance of promotion and increasing sales, this research is to find out "The Influence of the Use of Celebrity Endorsers on Consumers' Implusive Buying Behavior (Survey on Scarlett Body Whitening in Bandung City)". The method used in this research is descriptive method, collecting data through questionnaires. Test data through validity and reliability tests, statistical analysis through classical assumption tests, simple regression analysis and hypothesis testing. Based on the results of a partial hypothesis test (t test) shows that the use of celebrity endorsers has a significant effect on the Implusive Buying Behavior of Scarlett Body Whitening Consumers in Bandung, namely because tcount (9.378) > ttable (2.262). Based on the coefficient of determination test, it can be concluded that the use of celebrity endorsers has a significant influence on the Impulsive Buying Behavior of Scarlett Body Whitening Consumers with a percentage of 40.8%, while 59.2% is influenced by other factors not observed by this study. Keywords: Celebrity Endorser, Impulse Buying Behavior, Scarlett Body Whitening